Simulation of LEO Cubesat Constellation for Disaster Early Warning: An Equatorial Orbit Approach for Indonesia - Muslimin Mahmud; Asep Adang Supriyadi; Wahyudi Hasbi (Cita konsultindo, 2026)
The rapid expansion of Low Earth Orbit (LEO) satellite Technology offers new opportunities for is-land nations to build robust and autonomous communications infrastructure; however, research specifically examining the advantages of the 0° equatorial orbit for CubeSat constellations remains very limited despite its natural suitability for countries located along the equator. This study introduces a new constellation architecture optimized for the equatorial region, specifically Indonesia, by designing and simulating a ten-satellite 3U CubeSat system operating in a 0° equatorial orbit at 600 km. Using AGI Systems Tool Kit (STK) v11, we modeled orbital dynamics, Voice Repeater (VR) and Auto-matic Packet Reporting System (APRS) communication performance, and Inter-Satellite Link (ISL) stability from October 8 to 31, 2025, with a resolution of 30 seconds. The results show an average of 14 daily passes with a contact duration of 770 seconds and a link margin of 3.2 dB, enabling near real-time tactical communications. The main novelty lies in demonstrating that the 0° equatorial LEO constellation provides superior spatiotemporal consistency for Indonesia and can be implemented in other equatorial countries such as Brazil, the Democratic Republic of Congo, Uganda, and others, when compared to CubeSat designs in orbits above 0°. ISL connectivity achieved 99.1% reliability over 23 days, confirming continuous data flow even under ground segment disruptions. This study provides the first integrated demonstration of a VR, APRS, and ISL CubeSat network specifically optimized for equatorial regions, offering a viable and scalable model for disaster early warning systems in island nations. These findings indicate that equatorial orbit CubeSat constellations can serve as a strategic foundation for low latency, sovereign communication infrastructure in Indonesia and other developing countries that are rapidly advancing in the space sector.